Aplikacja materialnych i procesowych przesłanek prawnych, w sprawie o nieważność małżeństwa z powodu choroby alkoholowej pozwanego, na przykładzie wyroku trybunału III instancji c. Nowakowski z 6 maja 2013 r. - Nowakowski, Bartosz (Ius Matrimoniale, 2014)
On May 6, 2013 the Tribunal of third instance in Poznan, after considering a case of marriage nullity on the grounds of incapacity to assume the essential obligations of marriage for causes of a psychic nature on the part of the man (ca. 1095 n. 3 CIC), gave an affirmative sentence, what mean that marriage recognized for invalid. The author of article presents course of process in the first two instance and comment in detail sentence of third instance concentrating especially on material and procedural issues of the marriage canon law. On the first place he raises the problem of alcoholism and its influence on the validity of the marriage consensus. The theme is a presentation of the current issues of our times and concerns extremely gentle and difficult problems because of its subject, character and range.